NEMIS TILINDE SÓYLEW ÁMELIYATÍN INTERAKTIV TEXNOLOGIYALAR JÁRDEMINDE JEDELLESTIRIW - Sadikova, Azada Bekbergenovna (SCIENCE and SOCIETY, 2026)
This article examines the use of interactive technologies for speech development in German language teaching methods. It explores the concepts of "interactivity" and "interactive learning," and analyzes possible applications of this type of instruction in academic lyceums. The article’s scientific novelty lies in its exploration of the specific features of interactive methods for teaching German, drawing on various methodological and pedagogical works. It explores the essence of interactive learning, its types and methods, the methodological principles of this approach to teaching foreign languages, and analyzes teachers’ experiences in studying this issue.